Knowledge of Eye Care Workers among Students of a School of Optical Dispensing Technology in Birnin Kebbi, Nigeria - Monsudi, Kehinde Fasasi; Ayodapo, Abayomi Olusola; Oladigbolu, Kehinde K; Ogbu, Ike (Journal of College of Medical Sciences-Nepal, 2019)
Background: Eye care workers comprise of both clinical and non-clinical staff. For effective prevention of blindness and visual impairment the eye care health professionals must work in harmony. Also, the consumer of the eye care servicers must have good knowledge of these categories of workers to prevent financial loss, ocular morbidity from quackery and late hospital presentation. The main aim of this study is to assess the knowledge of students of school of optical dispensing technology, Birnin Kebbi, Nigeria about eye care workers. Methods: A cross-sectional study was conducted in August 2017, among students of School of Optical Dispensing Technology, Birnin Kebbi. A semi-structured questionnaire was used to elicit information which include socio-demographic characteristics, the knowledge of students about eye care team, the composition of eye care team, and the functions of eye care team members. Data entry and analysis was done using SPSS version 20. Results: 71 students participated, of which 44(62%) were males. The mean age of the participants was 23.6 ± 4.8years, with age range between 18-48years. Majority 32 (45.1%) were in the age group of 23 - 27years. Most 28 (39.4) of the participants were in year 2. More than two-third (97.2%) of the students agreed that eye care was a team work. About 98.2% of the respondents were aware that different cadres of eye care workers exist. Sources of information about eye care team among the study participants was mainly during workshop or hospital seminar 31 (43.7%) organised by the department of ophthalmology Conclusions: The awareness and knowledge about different cadres of eye care workers was high among the students. The participants agreed that eye care is a team work. The sources of informations about eye care team was hospital seminal/workshop organised by the department of ophthalmology.